STRATEGI CLINICAL GOVERNANCE DALAM PERBAIKAN MUTU PELAYANANRUMAH SAKIT (CLINICAL GOVERNANCE STRATEGY IN IMPROVING OFHOSPITAL CARE QUALITY) - Munifah Abdat (Dentistry Faculty, 2019)
It is important to prepare the pillars of clinical governance to achieve a quality of hospital servicesystem. The aim of implementing clinical governance is overall improvement based on improvingpatient-focused services, service satisfaction and continuous quality improvement. Clinical governanceis also paying attention to level of security both medical and non-medical related to risk management,having high performance, responsiveness and proactivity, and patient centered-care. Literature reviewregarding the quality of hospital services. Browse PubMed and the main organizational databasesabout clinical governance such as WHO and NHS Quality Improvement Scotland. A number of articlesrelated to hospital management strategies based own clinical governance have been reviewedincluding their application in several countries. The result showed clinical governance can be used todevelop a system to improve the quality of hosital services, carried out by integrating management,organizational, and clinical approaches simultaneously. The application of clinical governance builton 7 main pillars, namely Clinical Effectiveness, Risk Management, Patient Experience,Communication Effectiveness, Resources Effectiveness, Strategic Effectiveness, Learning Effectiveness.Conclusion. Development of clinical governance requires the active participation from all parties tocreate quality and professionalism in health services. Clinical governance ensuring that there was asystem to monitor of quality services that functioning properly, conduct the evaluation and the resultsof evaluations was used for improvement. Clinical governance will have a positive influence onincreasing patient trust as well as overall hospital management so its able to exist and compete inglobal competition.Keywords: Clinical governance, Quality of health services